Development of an animal model of hypothyroxinemia during pregnancy in Wistar rats - Wei Wei; Aihua Liu; Min Liu; Mingfeng Li; Xinghan Wu; Chuan Qin; Zhongyan Shan; Ling Zhang (Animal Models and Experimental Medicine)
Abstract Background Hypothyroxinemia is a subclinical thyroid hormone deficiency in which the mother has inadequate levels of T4 during pregnancy. The fetus relies entirely on the mother's T4 hormone level for early neurodevelopment. Isolated maternal hypothyroxinemia (IMH) in the first trimester of pregnancy can lead to lower intelligence, lower motor scores, and a higher risk of mental illness in descendants. Here, we focus on the autism‐like behavior of IMH offspring. Methods The animals were administered 1 ppm of propylthiouracil (PTU) for 9 weeks. Then, the concentrations of T3, T4, and thyroid‐stimulating hormone (TSH) were detected using enzyme‐linked immunosorbent assay (ELISA) to verify the developed animal model of IMH. We performed four behavioral experiments, including the marble burying test, open‐field test, three‐chamber sociability test, and Morris water maze, to explore the autistic‐like behavior of 40‐day‐old offspring rats. Results The ELISA test showed that the serum T3 and TSH concentrations in the model group were normal compared with the negative control group, whereas the T4 concentration decreased. In the behavioral experiments, the number of hidden marbles in the offspring of IMH increased significantly, the frequency of entering the central compartment decreased, and the social ratio decreased significantly. Conclusion The animal model of IMH was developed by the administration of 1 ppm of PTU for 9 weeks, and there were autistic‐like behavior changes such as anxiety, weakened social ability, and repeated stereotyping in the IMH offspring by 40 days.